Finding a place from the Southern borders: archaeology in Chile, memory and past-present of dictatorships - Fuenzalida, Nicole (2023)
In Chile, the approach towards the past is directly associated to the shapes taken by the diverse recounts of the dictatorial past. In particular, regarding the conversion of sites, where horror took place, into places of memory. Archaeology found its place in these processes of accompaniment led by the collectives that manage the spaces. This paper examines the place of academic and personal enunciation of the archaeology of dictatorships in relation to the ethical and political outlined by the coexistence of the structural violence and the struggles led by survivors and witnesses. For this purpose, we present data of the Chilean academic context from an historical standpoint and provide some archaeological projects from that same perspective. A great part of the discussion advocates for the importance of engaging this archaeological practice in current political scenarios by establishing it as a resource to update the debate on the memory of contemporary political violence.